ANTICORRUPTION POLICY AS A FACTOR IN COUNTERING CORPORATE FRAUD IN OIL COMPANIES - I. Snimtshikova; A. Melnikov; J. Chugayeva (Вестник Северо-Кавказского федерального университета, 2022)
This article discusses the main types of corporate fraud ofoil companies in Russia. Indicators of abuse and violation of the anti-corruption policy of oil industry enterprises are highlighted. It was emphasized that the ineffective work of economic security units and the widespread corruption in oil companies contribute to an annual increase in financial losses. The study presents the main methods of theft of oil products in the segments of oil production, oil refining and sale of oil products. The authors identified the main causes of corporate fraud in the theft of oil and oil products. The article established that the main task of the anti-corruption policy is to prevent corporate fraud by monitoring precursors, indicators ofpossible abuse.